ABIOTIC FACTORS INFLUENCING MANTANGAN (Merremia peltata) INVASION IN BUKIT BARISAN SELATAN NATIONAL PARK - Jani Master; Soekisman Tjitrosoedirdjo; Ibnul Qayim (SEAMEO BIOTROP, 2016)
Some areas in Bukit Barisan Selatan National Park have serious environmental problems related to the invasion of Merremia peltata (Family: Convolvulaceae). This study investigated abiotic factors influencing the invasion. The research compared abiotic conditions in three forest locations with different invasion levels: severe, moderate, and mild. Measured abiotic factors included percentage of tree canopy cover, microclimate variables (temperature and humidity), elevation above sea level, and the physical and chemical properties of the soil surface. In this study, canopy cover was categorized as an abiotic factor because it affects the amount of light reaching the forest floor. A post-hoc Duncan's Multiple Range Test (DMRT) was performed to determine significant differences (p < 0.05) among abiotic variables. Additionally, correlation analysis and multiple linear regression were conducted to evaluate the relationships between abiotic factors and the level of M. peltata invasion. Multiple regression analysis showed that canopy cover significantly (p < 0.05) affected the invasion. Based on the generated model, a 1% increase in canopy cover would decrease the M. peltata invasion by approximately 2.8%. Soil nutrient analysis through multiple linear regression revealed that the C/N ratio, and concentrations of P₂O₅, Ca, Mg, and Na significantly (p < 0.05) influenced invasion level. An increase in C/N ratio and concentrations of P₂O₅ and Ca were correlated with a reduction in invasion, whereas increases in Mg and Na concentrations were associated with higher invasion levels. Overall, the invasion of Merremia peltata in Bukit Barisan Selatan National Park was influenced by an open forest canopy and was associated with high concentrations of Na and Mg in the soil of invaded areas.